Introduction of water footprint assessment approach to enhance water supply management in Malaysia - Moni S.N.; Aziz E.A.; Malek M.A. (American Institute of Physics Inc., 2023)
Presently, Water Footprint (WF) Approach has been used to assess the sustainability of a product's chain globally but is lacking in the services sector. Thus, this paper aims to introduce WF assessment as a technical approach to determine the sustainability of water supply management for the typical water supply treatment process (WSTP) used in Malaysia. Water supply is one of the pertinent services and most of WF accounting begins with data obtained from the water supply treatment plant. Therefore, the amount of WF will be accounted for each process of WSTP in order to determine the water utilization for the whole process according to blue, green and grey WF. Hence, the exact amount of water used in the process can be measured by applying this accounting method to assess the sustainability of water supply management in Malaysia. Therefore, the WF approach in assessing sustainability of WSTP could be implemented. 2017 Author(s).